Alexithymia and Body Image in Saudi Arabian Females (University Students): Preliminary Data - Muwafak H. Al-Eithan; Hend Alsulaiman; Iman M. Al-Eithan (Dubai Medical Journal)
Introduction: Alexithymia has been the focus of much recent research in relation to emotional regulation and eating problems amongst psychological disorders. It is dealing with difficulties in processing, expressing, and awareness of emotion. Body image has also been researched, especially amongst women, and its relation emotion. Objective: The aim of this exploratory study is to examine the presence of alexithymia and how this is related to body image amongst a group of female Saudi University students. Methods: 152 Arabic female students from a local University participated in the study. The Toronto Alexithymia Scale-20 (TAS-20 Arabic), the Therapeutic Alexithymia scale (PTA Scale) short scale, body image scale, and figure body image scale were all used in the study. Results: The results showed that there is significant correlation between TAS and body image scale. Further, results showed that body image scale is best predictor of alexithymia in regression analysis. Discussion: Alexithymia has not been studied in university students in KSA. We also explored its relationship to body image and found there is a significant correlation. Alexithymia is present and needs much research in this sample and beyond, in both clinical and non-clinical groups. Conclusion: This is the first study in an Arabic population to show the alexithymia is prevalent amongst this sample and it is significantly related to poor body image. Further studies are suggested to explore further psychological variables related to body image and eating problems, as well as on clinical samples is indicated.